2018
DOI: 10.18203/2320-6012.ijrms20181293
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of blood component cross-matching and their utilization in a tertiary care hospital of Jammu region

Abstract: Background: Transfusion of donated blood remains the mainstay of treatment for a wide range of medical and surgical conditions. Although it can save life, but transfusion of blood is not without risk. Clinicians should cautiously assess the appropriateness of indications before requesting various blood components thereby preventing misuse of blood and unnecessary exposure of patient to various transfusion transmitted infections and antibodies production. This study was conducted to determine the pattern of who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Our study revealed an overall transfusion probability of 33%, as compared to studies by Devi et al, Kaur et al, and one in the Jammu region, which revealed %T values of 97.2%, 79%, and 88.8%, respectively, showing an effective utilization of blood [13][14][15].…”
Section: Discussionsupporting
confidence: 53%
“…Our study revealed an overall transfusion probability of 33%, as compared to studies by Devi et al, Kaur et al, and one in the Jammu region, which revealed %T values of 97.2%, 79%, and 88.8%, respectively, showing an effective utilization of blood [13][14][15].…”
Section: Discussionsupporting
confidence: 53%
“…Bashwari LA et al 12 2.9 Benin 2.2 Ibrahim SZ et al 13 3.9 Jayarancee S 14 5.0 Subramanian A et al 15 2.5 Yasmeen I et al 16 1.12 Mangwana S et al 17 1.34 Raghuwanshi B et al 18 6.31 Kuchhal A et al 9 1.8 Present study…”
Section: Studies C/t Ratio(total)mentioning
confidence: 69%
“…Blood being a biologic agent, is associated with both infectious and noninfectious complications. 2,3 Before prescribing blood or blood products for a patient, it is always essential to weigh up the risks of transfusion against the risks of not transfusing. The safety and effectiveness of transfusion depend on two key factors: supply of blood and blood products that are safe, accessible at reasonable cost and adequate to meet national needs and the appropriate clinical use of blood and blood products.…”
Section: Introductionmentioning
confidence: 99%